Harnessing Public Research for Innovation in the 21st Century An International Assessment of Knowledge Transfer Policies - Arundel, Anthony; Athreye, Suma; Wunsch-Vincent, Sacha (Social Sciences, 2021)
Universities and public research institutes play a key role in enabling the application of scientific breakthroughs and innovations in the marketplace. This book, available also as Open Access, suggests the most effective policies to support the transfer of knowledge to firms in order to boost economic growth and foster innovation.